MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN TEAMS GAMES TOURNAMENTS BERBANTUKAN DOMINO TRIGONOMETRI - Ri 1, Andy Sapta2 Fazqi Marchi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract This study aims to determine whether there is a domino effect trig-assisted TGT on learning outcomes of students at SMAN 1 Aek Kuasan. The research instrument consists of consists of an essay test that includes as many as 5 pieces and achievement test questions at the end of the cycle by 5 questions. The results of the study in the first cycle shows the average student learning outcomes 72.25 with 72.2% completeness percentage. The results of the study on cycle 2 gained an average of 80.5 student learning outcomes with the percentage of 91.7%. this study concluded that by using trigonometry domino berbantukan TGT can improve student learning outcomes in class X SMA Negeri 1 Aek Kuasan academic year 2013/2014. Keywords: Teams Games Tournaments, Domino Trigonometry, Trigonometry